Nonplatinum‐based therapy with Paclitaxel and Capecitabine for advanced squamous cell carcinomas of the anal canal: A population‐based Danish anal cancer group study - Christina Glismand Truelsen; Eva Serup‐Hansen; Katrine Smedegaard Storm; Birgitte Mayland Havelund; Camilla Skovhus Kronborg; Karen‐Lise Garm Spindler (Cancer Medicine, 2021)
Abstract Background First‐line platinum‐based therapy for advanced squamous cell carcinomas of the anal canal (SCCA) implies a risk of substantial side effects, and data on second‐line treatment options are limited. Paclitaxel and Capecitabine are a well‐known regimen with a moderate toxicity profile, but its efficacy has not been evaluated. Methods We conducted a retrospective study using Danish Hospital Registers of patients treated with Paclitaxel and Capecitabine for inoperable, recurrent, or advanced metastatic SCCA in Denmark, between January 2000 and July 2018. Results A total of 52 patients met the eligibility criteria. Median age was 60.7 years (range 42–83). Efficacy was observed, with an overall response rate in patients receiving first‐line (N = 28) and second‐line (N = 23) Paclitaxel and Capecitabine of 39.3% (2 with complete responses) and 17.4%, respectively. Median progression‐free survival (PFS) was 4.5 months (95% CI 3.3–5.9) and 3.8 months (95% CI 2.4–5.5) with OS of 6.7 months (95% CI 5.9–8.5) and 5.9 months (95% CI 3.9–14), respectively. Performance status ≥2 and neutrophil to lymphocyte ratio ≥4 were significantly associated with a short PFS. Conclusion This study recognizes Paclitaxel and Capecitabine as a potential regimen for advanced SCCA, when recommended first‐line therapy is not feasible or as a potential second‐line treatment after failure of platinum‐based chemotherapy.